Field experiment on a vegetation-wicking geotextile-reinforced base for a permeable sidewalk - Xie, Xiangbin; Yang, Gengxin; Liu, Zhao; Tang, Yelin; Chu, Jingying; Wen, Wenhao; Chen, Aolong; Guo, Jun; Luo, LeiKe (Frontiers in Built Environment, 2024)
Wicking geotextile have proven effective in reducing water content in road bases under both saturated and unsaturated conditions, thereby increasing granular base strength and mitigating moisture-related damage to pavement. Despite its effectiveness in paved roads, the use of wicking geotextiles in permeable road and sidewalk, particularly in areas requiring robust drainage like sponge cities, is not well-explored. In "sponge city" roads, moisture content fluctuations and subsequent damage to the structure often cause concern and the wicking geotextile's drainage could be a potential solution. Therefore, this study aims to investigate and quantify the effectiveness of wicking geotextiles in reducing the moisture content and improving resilient modulus of permeable sidewalk base layers. The moisture contents of un-stabilized, one-directional, and two-directional wicking geotextile stabilized bases under permeable paving bricks were monitored with 7 to 10 days interval for over a year. An analytical approach to reconstruct daily moisture content in the base layer was proposed based on simulated rainfall saturation test. This approach further assesses the enhancements in resilient modulus due to the drainage capabilities of wicking geotextiles. The experimental results indicated that two-directional wicking geotextile outperform its one-directional counterparts and both wicking geotextiles outperformed the control condition in terms of drainage efficiency. By reconstructing the daily moisture content and utilizing the relative damage model, the two-directional wicking geotextile significantly improved the annual equivalent resilient modulus of the base layer under permeable paving bricks.